Autophagy and Cancer: a literature review (Research, Society and Development, 2020)
Autophagia, or macroautophagy, is a phenomenon of cellular degradation and recycling that occurs constitutively at low levels in eukaryotic cells. Thasgained prominence as a pathway of mobilization of metabolic substrates that allow cancer cells to survive microenvironments with low nutrient supply or under conditions of oxidative stress, where the role of proteins such as beclin-1 and LC3B has been widely researched in various types of cancer. The aim of the present study was to review the literature on the performance of the autophagy process and its relationship with the development of cancer through autophagia. To design This article, a bibliographic survey was carried out covering the period from 1998 to 2019. Google academic, Scielo, LIlacs and Medline research portals were used. In this review, it is the result that autophagy has a dual role in cancer, as it can prevent tumor initiation through the suppression of chronic damage, inflammation, accumulation of damaged organelles and genomic instability, but Autophagia also maintains the Mitochondrial metabolic functions that provide nutrients for the growth of tumor cells, creating aggressive cancers.